2005
DOI: 10.1111/j.1365-2958.2005.04878.x
|View full text |Cite
|
Sign up to set email alerts
|

The growth rate of Mycobacterium smegmatis depends on sufficient porin‐mediated influx of nutrients

Abstract: SummaryMycobacteria have a unique outer membrane (OM) that is thicker than any other known biological membrane. Nutrients cross this permeability barrier by diffusion through porins. MspA is the major porin of Mycobacterium smegmatis . In this study we showed that three paralogues of MspA, namely MspB, MspC and MspD are also porins. However, only the mspA and mspC genes were expressed in the wild-type strain. None of the single deletion mutants displayed a significant OM permeability defect except for the mspA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
157
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 101 publications
(167 citation statements)
references
References 51 publications
10
157
0
Order By: Relevance
“…Proteins were extracted from M. smegmatis by using 2% SDS in PBS at 40°C as described (13). Proteins were analyzed in Western blots by using specific antibodies raised against MctB (5D1.23), MymT (kindly provided by Ben Gold), and horseradish peroxidase-coupled anti-mouse or anti-rabbit secondary antibodies as described (30). For further details, see SI Appendix.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were extracted from M. smegmatis by using 2% SDS in PBS at 40°C as described (13). Proteins were analyzed in Western blots by using specific antibodies raised against MctB (5D1.23), MymT (kindly provided by Ben Gold), and horseradish peroxidase-coupled anti-mouse or anti-rabbit secondary antibodies as described (30). For further details, see SI Appendix.…”
Section: Methodsmentioning
confidence: 99%
“…The CpnT NTD-HA-His6 protein was purified from the M. smegmatis strain ML1910, which lacks all known endogenous porin genes and conditionally expresses cpnT NTD , to avoid contamination with M. smegmatis and M. tuberculosis pores. The porin-deletion mutant ML1910 is not viable without expression of cpnT NTD , indicating that it does not have outer membrane proteins with significant channel activity other than the Msp porins (25). The CpnT NTD protein was extracted from the M. smegmatis porin-deletion mutant with SDS and purified by Ni (II)-affinity followed by anion-exchange chromatography.…”
Section: Significancementioning
confidence: 99%
“…Consecutive deletions of the two porin genes mspA and mspC reduced the number of pores 15-fold compared to wild-type M. smegmatis. The loss of porins lowered the permeability for glucose 75-fold and, concomitantly, the growth rate of M. smegmatis on plates and in liquid medium dropped drastically (Stephan et al, 2005). This showed for the first time that the porinmediated influx of hydrophilic nutrients limited the growth rate of porin mutants.…”
Section: Transport Across Mycobacterial Outer Membranesmentioning
confidence: 80%
“…However, it is unknown which and how many nutrients are in low supply in the M. smegmatis porin mutants. Since MspA could not be expressed in M. smegmatis above wild-type levels (Stephan et al, 2005), it is also not clear whether the influx of nutrients really limits the growth rate of wild-type mycobacteria as suggested earlier (Jarlier & Nikaido, 1990). The fact that the lack of the MspA and MspC porins also caused a reduced uptake of phosphates and slower growth on low-phosphate plates (Wolschendorf et al, 2007) indeed suggested that the slow uptake of essential hydrophilic nutrients other than the carbon source may also contribute to the slow growth of M. smegmatis porin mutants.…”
Section: Transport Across Mycobacterial Outer Membranesmentioning
confidence: 99%
See 1 more Smart Citation